2021
DOI: 10.3390/microorganisms9020447
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Binding of Periplasmic Protein GltB Activates GtrS-GltR Two-Component System in Pseudomonas aeruginosa

Abstract: A two-component system GtrS-GltR is required for glucose transport activity in P. aeruginosa and plays a key role during P. aeruginosa-host interactions. However, the mechanism of action of GtrS-GltR has not been definitively established. Here, we show that gltB, which encodes a periplasmic glucose binding protein, is essential for the glucose-induced activation of GtrS-GltR in P. aeruginosa. We determined that GltB is capable of binding to membrane regulatory proteins including GtrS, the sensor kinase of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 82 publications
1
8
0
Order By: Relevance
“…The comparison to this set extracted from 22 previous studies and composed of 59 known binding sites concerning 21 RRs showed that the vast majority were effectively retrieved, often resulting in very highly enriched peaks (Figure S2), further validating our approach. We then compared our results to the previously reported ChIP-seq studies on RRs for which we detected binding sites (PhoB, GacA, GltR, PhoP, CzcR, DsbR and BfmR) (Bielecki et al, 2015;Fan et al, 2021;Huang et al, 2019;Xu et al, 2021;Yang et al, 2021;Yu et al, 2021). Here again, there was a strong overlap in detected binding sites between the DAP-seq data and the six different ChIP-seq studies, as well as highly similar identified DNA motifs (Figure S3).…”
Section: Dap-seq Allows the Investigation Of The Tcss Regulatory Networksupporting
confidence: 61%
See 2 more Smart Citations
“…The comparison to this set extracted from 22 previous studies and composed of 59 known binding sites concerning 21 RRs showed that the vast majority were effectively retrieved, often resulting in very highly enriched peaks (Figure S2), further validating our approach. We then compared our results to the previously reported ChIP-seq studies on RRs for which we detected binding sites (PhoB, GacA, GltR, PhoP, CzcR, DsbR and BfmR) (Bielecki et al, 2015;Fan et al, 2021;Huang et al, 2019;Xu et al, 2021;Yang et al, 2021;Yu et al, 2021). Here again, there was a strong overlap in detected binding sites between the DAP-seq data and the six different ChIP-seq studies, as well as highly similar identified DNA motifs (Figure S3).…”
Section: Dap-seq Allows the Investigation Of The Tcss Regulatory Networksupporting
confidence: 61%
“…Peak lists from ChIP-seq experiments with PhoB, GacA, CzcR, GltR, PhoP, DsbR and BfmR were used to retrieve all peak summit locations (Bielecki et al, 2015;Fan et al, 2021;Huang et al, 2019;Xu et al, 2021;Yang et al, 2021;Yu et al, 2021). Peak summit positions were averaged between replicates and used to infer gene targets using the genome-wide promoter regions defined above with the Intersect tool from BEDTools (Quinlan and Hall, 2010) on the corresponding genomes: PAO1 (Fan et al, 2021;Huang et al, 2019;Xu et al, 2021;Yu et al, 2021) or PA14 (Bielecki et al, 2015;Yang et al, 2021). For DNA motif determination, peak regions were extended by 50bp on each side of the summits and retrieved using the GetFastaBed tool from BEDTools (Quinlan and Hall, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Western blot analysis were performed as described previously with some modifications [42][43][44]. Generally, to examine the production of fusion proteins (i.e., p-PhoB-Flag, p-(D)-PhoB-Flag) in P. aeruginosa, overnight LPM cultures of the indicated strains were diluted to OD 600 ≈ 0.05 with fresh LPM medium.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…The response of several Escherichia coli chemoreceptors to sugars is based on the recognition of sugar-loaded SBPs ( 11 ). In addition, PctA of P. aeruginosa was shown to sense glucose through the periplasmic ligand binding protein, GltB ( 48 ). Therefore, our finding that dCache chemoreceptor McpA can directly bind sugars through a combination of both pockets may serve as a reference for analogous studies for sugar chemotaxis in bacteria.…”
Section: Discussionmentioning
confidence: 99%